Controle pid fuzzy adaptativo com estabilidade robusta por enxame de partículas multiobjetivo - Costa, Edson Bruno Marques (2016)
An adaptive fuzzy digital PID controller design methodology via multiobjective particle swarm optimization (MOPSO) based on robust stability criterion, is proposed. The plant to be controlled is modelled considering a Takagi-Sugeno (TS) fuzzy structure from input-output experimental data, by using the fuzzy C-Means clustering algorithm (antecedent parameters estimation) and fuzzy recursive least squares algorithm (consequent parameters estimation), respectively. An adaptation mechanism was formulated as a MOPSO problem for online tuning of the fuzzy digital PID controller parameters based on the fuzzy model parameters obtained recursively and the gain and phase margins specifications. Computational results for adaptive fuzzy digital PID control of a thermal plant with time varying delay is presented to illustrate the efficiency and applicability of the proposed methodology.